2009
DOI: 10.1016/j.ssci.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on the influence of stress caused by the need to combine work and family on occupational accidents in working women

Abstract: Keywords:Occupational accident Work Family Stress WomenThe influx of a large number of women into the workforce involves the need for these women to combine family and work responsibilities. Multiple roles lead to work-family conflict. This study analyzes the influence of work-family conflict on the causes of minor occupational accidents suffered by working women. A survey was done on working women in the Madrid region, who had suffered a minor occupational accident in 2004. The main finding was that nearly ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The resulting lack of time could be a contributor to the negative association between perceived stress and health behavior within the family. To overcome these problems, a better balance of family and career for working mothers and a more equitable division of responsibilities and housework between the parents seems warranted (Martín-Fernández, de los Ríos, Cazorla, & Martínez-Falero, 2009). …”
Section: Inter-individual Effects Of Perceived Stress On Physical Actmentioning
confidence: 99%
“…The resulting lack of time could be a contributor to the negative association between perceived stress and health behavior within the family. To overcome these problems, a better balance of family and career for working mothers and a more equitable division of responsibilities and housework between the parents seems warranted (Martín-Fernández, de los Ríos, Cazorla, & Martínez-Falero, 2009). …”
Section: Inter-individual Effects Of Perceived Stress On Physical Actmentioning
confidence: 99%
“…Most of these nurses are women (98.8%), and 33% of female nurses are married (Yang, Pan, & Yang, 2004). Martin-Fernandez, Ignacio de Los, Cazorla, and Martinez-Falero (2009) found that working women spend more time caring for children and completing housework than their husbands. In European countries, 25% of women aged 18 years and older care for children, but only 9% of men are responsible for child care (Martin-Fernandez et al, 2009).…”
Section: Work Stress and Health Statusmentioning
confidence: 99%
“…Martin-Fernandez, Ignacio de Los, Cazorla, and Martinez-Falero (2009) found that working women spend more time caring for children and completing housework than their husbands. In European countries, 25% of women aged 18 years and older care for children, but only 9% of men are responsible for child care (Martin-Fernandez et al, 2009). Furthermore, working married women experience higher levels of family stress compared to married men.…”
Section: Work Stress and Health Statusmentioning
confidence: 99%
“…With increasing trend in the participation of women in the work force and due to the competing demands between work and family, the metaphor of work-family conflict (WFC) as an increasing pressure in professional life has emerged. 3 , 4 WFC seems to be more common in women than men due to more overload, stress, and work-family conflicts. 5 …”
Section: Introductionmentioning
confidence: 99%